Solve the equation
1. 2x – 3 =7
2. 7y + 9 = 16
3. 2 ( x – 3 ) = 15
4. 2x-3 = x +2
5. 6x = 12
Answers
Step-by-step explanation:
please give me some thanks please
![](https://hi-static.z-dn.net/files/dc8/cc5cd777f482b87e662479f0e9326f03.jpg)
![](https://hi-static.z-dn.net/files/dbb/2bdb82abcc42db5737f4be0108a17c55.jpg)
![](https://hi-static.z-dn.net/files/dc1/27ec6c42c753f1c262675ac67e0bae03.jpg)
![](https://hi-static.z-dn.net/files/d22/d0a2fbea6122321e226894812d2352c7.jpg)
![](https://hi-static.z-dn.net/files/d04/7760538a45bf84147fb1838819066a47.jpg)
Question :-
Solve the equation :
1. 2x - 3 = 7
Answer :-
The required number is 5.
Step-by-step explanation:
⇒ 2x - 3 = 7
⇒ 2x = 7 + 3
⇒ 2x = 10
⇒ x = 10/2
⇒ x = 5
V E R I F I C A T I O N :-
- 2x - 3 = 7
By simplifying the L.H.S :-
⇒ 2x - 3
⇒ 2*5 - 3
⇒ 10 - 3
⇒ 10
∴ L.H.S = R.H.S
Hence, Verified!
2. 7y + 9 = 16
Answer :-
The required number is 1.
Step-by-step explanation:
⇒ 7y + 9 = 16
⇒ 7y = 16 - 9
⇒ 7y = 7
⇒ y = 7/7
⇒ y = 1
V E R I F I C A T I O N :-
- 7y + 9 = 16
By simplifying the L.H.S :-
⇒ 7y + 9
⇒ 7*1 + 9
⇒ 7 + 9
⇒ 16
∴ L.H.S = R.H.S
Hence, Verified!
3. 2(x - 3) = 15
Answer :-
The required number is 15.
Step-by-step explanation:
⇒ 2(x - 3) = 15
⇒ 2x - 6 = 15
⇒ 2x = 15 + 6
⇒ 2x = 21
⇒ x = 21/2
⇒ x = 10.5
V E R I F I C A T I O N :-
- 2(x - 3) = 15
By simplifying the L.H.S :-
⇒ 2(10.5 - 3)
⇒ 2(7.5)
⇒ 15
∴ L.H.S = R.H.S
Hence, Verified!
4. 2x - 3 = x + 2
Answer :-
The required number is 5.
Step-by-step explanation:
⇒ 2x - 3 = x + 2
⇒ 2x - x - 3 = 2
⇒ x - 3 = 2
⇒ x = 2 + 3
⇒ x = 5
V E R I F I C A T I O N :-
- 2x - 3 = x + 2
By simplifying the L.H.S an R.H.S :-
- L.H.S :-
⇒ 2x - 3
⇒ 2*5 - 3
⇒ 10 - 3
⇒ 7
- R.H.S
⇒ x + 2
⇒ 5 + 2
⇒ 7
∴ L.H.S = R.H.S
Hence, Verified!
5. 6x = 12
Answer :-
The required number is 2.
Step-by-step explanation:
⇒ 6x = 12
⇒ x = 12/6
⇒ x = 2
V E R I F I C A T I O N :-
- 6x = 12
By simplifying the L.H.S :-
⇒ 6x
⇒ 6*2
⇒ 12
∴ L.H.S = R.H.S
Hence, Verified!